Inequity in Health Services Utilization in Economically Underdeveloped Regions of Northeast China - Xin Zhang; Xin Zhang; Ning Ning; Ning Ning; Hongguo Zhou; Linghan Shan; Linghan Shan; Yanhua Hao; Yanhua Hao; Mingli Jiao; Mingli Jiao; Libo Liang; et al. (Frontiers Media S.A., 2022)
BackgroundThe Chinese health system has long been committed to eliminating inequalities in health services utilization. However, few studies have analyzed or measured these inequalities in economically underdeveloped regions in China.MethodsA total of 6,627 respondents from 3,000 households in Heilongjiang Province were extracted from the Sixth National Health Services Survey. We measured horizontal inequity in both 2-week outpatient rate and annual inpatient rate, and then identified the factors contributing to inequality.ResultsThe horizontal inequity indices of the 2-week outpatient and annual impatient rates in Heilongjiang Province were 0.0586 and 0.1276, respectively. Household income, health status, place of residence, basic medical insurance, and commercial health insurance were found to be the main factors affecting inequality in health services utilization. The contributions of household income to these two indices were 184.03 and 253.47%, respectively. Health status factors, including suffering from chronic disease, limitations in daily activities, and poor self-rated health, played positive roles in reducing inequality in these two indices. The contributions of place of residence to these two indices were 27.21 and −28.45%, respectively. Urban Employee Basic Medical Insurance made a pro-rich contribution to these two indices: 56.25 and 81.48%, respectively. Urban and Rural Resident Basic Medical Insurance, Urban Resident Basic Medical Insurance, New Rural Cooperative Medical Scheme, and other basic medical insurance made a pro-poor contribution to these two indices: −73.51 and −54.87%, respectively. Commercial health insurance made a pro-rich contribution to these two indices: 20.79 and 7.40%, respectively. Meanwhile, critical illness insurance made a slightly pro-poor contribution to these two indices: −4.60 and −0.90%, respectively.ConclusionsThe findings showed that the "equal treatment in equal need" principle was not met in the health services utilization context in Heilongjiang Province. To address this issue, the government could make policy changes to protect low-income populations from underused health services, and work to improve basic medical insurance, critical illness insurance, and social security systems.